Defining the glucosylceramide population of C. elegans - Xatse, Mark A.; Olsen, Carissa Perez (Frontiers in Physiology, 2023)
Glucosylceramides (GlcCer) are lipids that impact signaling pathways, serve as critical components of cellular membranes, and act as precursors for hundreds of other complex glycolipid species. Abnormal GlcCer metabolism is linked to many diseases, including cancers, diabetes, Gaucher disease, neurological disorders, and skin disorders. A key hurdle to fully understanding the role of GlcCer in disease is the development of methods to accurately detect and quantify these lipid species in a model organism. This will allow for the dissection of the role of this pool in vivo with a focus on all the individual types of GlcCer. In this review, we will discuss the analysis of the GlcCer population specifically in the nematode Caenorhabditis elegans, focusing on the mass spectrometry-based methods available for GlcCer quantification. We will also consider the combination of these approaches with genetic interrogation of GlcCer metabolic genes to define the biological role of these unique lipids. Furthermore, we will explore the implications and obstacles for future research.